Environmental Influences on Caribbean Fish Catch. (28th March 2011) - Jury, Mark R.
Abstract : A Caribbean fishery index is used to identify contrasting environmental conditions in atmosphere and ocean reanalysis fields associated with high- and low-catch years over the period 1971–2004. A number of composite features are noted: cooler surface temperatures and warmer, drier weather across the southern half of the Caribbean favors higher catch rates. There is a ridge of elevated sea level on 16°N. South of the ridge the Caribbean Current is strengthened while north of the ridge anomalous eastward currents flow past the Antilles Islands. The atmospheric Hadley circulation weakens in years of high catch and tropical cyclones are rare. This paper uncovers basin-scale forcing of aggregate fish catch, reflecting a north-south gradient in land-atmosphere hydrology, and composite oceanographic differences based on reanalysis data. In addition, seasonal and interannual cycles of ocean productivity are investigated using satellite ocean color. Summertime upwelling along the coast of Venezuela joins fresher waters from the North Brazil Current to infuse the Caribbean ecosystem with higher nutrients.